The role of policy priorities and targeting in the spatial location of participation in Agri-Environmental Schemes in Emilia-Romagna (Italy). (September 2015) - Raggi, M.; Viaggi, D.; Bartolini, F.; Furlan, A.
Highlights: Regional priorities are significant in affecting the participation in measure 214. Spatial component are significant in improving the explanatory ability of the model. Explanatory variables were sharply differentiated by sub-measures. Abstract: The objective of the paper is to understand the determinants of the spatial location of participation in Agri-Environmental Schemes and, in particular, to understand the interplay between structural determinants, priority criteria and spillover effects in guiding participation. As a first step, the paper seeks to conceptualise the issue based on the existing literature. Thereafter, an econometric model is used to provide an empirical application on data regarding participation in measure 214 of the Rural Development Programme 2007–2013 in an Italian region (Emilia-Romagna). The results show that both priority scores and the spatial dimension are significant in affecting participation.